EFFECT OF MAITLAND MOBILIZATION AND CORE STABILIZATION EXERCISES IN PATIENTS WITH LUMBAR DISC HERNIATION (Journal of Medical & Health Sciences Review, 2025)
Background: Lumbar Disc Herniation (LDH) is one of the most common complain of the working age population, there are many factors that contributing to LDH. The LDH can alter the biomechanics of spine including the disc producing abnormal gait patterns & promoting low back pain. Both Core Stability Exercises and Maitland Techniques considered effective manual therapy techniques in managing of CLBP due to LDH. Yet difference in efficacy between both techniques is not known. Maitland posteroanterior mobilization (MM), which is widely used all over the world, is still unknown. The purpose of this study was to retrospectively analyze and compare the efficacy of these 2 treatments in patients with LDH as to provide a basis for the clinical treatment of LDH.Aims and Objectives: The purpose of this study was to compare between the efficacy of Core Stability Exercise and Maitland Mobilization Techniques on pain level, flexibility and Range of Motion in patients to reduce pain, to improve flexibility and QOL of patients with LDH.Methods: The study conducted in hospitals of Faisalabad over the period of 3 to 4 months after obtaining approval from the ethical committee of College of Rehabilitation Sciences. Sample size of 42 patients generated by G Power. Convenient sampling technique used to select patients. Patients allocated into two group referred as group A and group B. Core Stability Exercise intervention given to group A and Maitland Mobilization given to group B. The treatment given for 3 times on alternate days a week for 4 weeks. Numeric Pain Rating Scale (NPRS), goniometer and LEFS was the outcome measures. Pre and post treatment readings taken by using NPRS, goniometer and Lower extremity functional index of the patients after disc herniation repair. The measurements taken at baseline and after 4th week.Results: Core stability exercises may be the better choice for patients whose main concern is pain and limited daily function. Maitland mobilization might be more useful when joint stiffness or limited spinal flexibility is the biggest problem.Conclusion: This study found that both core stability exercises and Maitland mobilization help reduce pain, improve spinal movement, and support better lower limb function in patients with lumbar disc herniation. Core stability training, however, showed slightly better results for pain relief and functional gains. These results can help guide physiotherapists in choosing the best treatment plan for each patient based on their specific symptoms and limitations.